PROJECT BASED LEARNING SEBAGAI UPAYA UNTUK MENUMBUHKAN KEMANDIRIAN DAN TANGGUNG JAWAB BELAJAR SISWA SEKOLAH DASAR - Dhelia, Nur; Nona; Hasanah, Azzahrassyifa; Amin, Muhammad; Suriansyah, Ahmad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Project-Based Learning (PjBL) is an educational approach that focuses on students as the main focus of the learning process through real and meaningful project activities. This article discusses the application of PBL as an effort to foster independence and awareness of learning responsibilities among elementary school students. By applying this method, students not only gain insight, but are also actively involved in managing tasks independently and taking responsibility for their learning outcomes. Research findings show that PBL is effective in increasing learning motivation, independence in completing tasks, and awareness of responsibility for the learning process and outcomes of students. The consequence of this study is the need for teachers to adopt the PBL method in learning in order to develop independence and responsibility from an early age.